INEQUALITY ECONOMIC GROWTH AND DISTRIBUTION IN THE EDUCATION SECTOR : PERIOD (2002 - 2013) - Palomino Silva, Julio Andrés (2014)
During the period 2002 - 2013 Peru experienced significant economic growth, with excellent macroeco-nomic indicators and financial stability. This growth was mainly due to a magnificent international context where increasing demand of minerals and export high mineral prices thereof converged. This has allowed the State to have a lot of resources; both the general budget of the republic as sectorial budgets had significant increases. In response, this study asks to what extent the economic growth helped to reduce the existing distributive inequality in our country, and focuses on the analysis of budgets in the education sector and spe-cifically, the budgets allocated to public universities. One of the highlights research finding is that; under current regulations, based on the distribution of the canon, several universities have seen their budgets increased exponentially, while others have done so in small percentage. The research concludes that the Peruvian economic growth has deepened distributive inequality in public higher education.